Determination of total phenolic content, antioxidant activity and antifungal effects of Thymus vulgaris, Trachyspermum ammi and Trigonella foenum-graecum extracts on growth of Fusarium solani - Nateqi, Masoud; Mirghazanfari, Sayid Mahdi (Cellular and Molecular Biology, 2018)
Ajowan, thyme and fenugreek are spice and aromatic crops with a number of medicinal properties which are known as important sources of essential phytochemicals. The purpose of this study was to investigate the antioxidant capacity, total phenolic content and antifungal activities of these plant extracts on growth of Fusarium solani, an important plant pathogen, soil saprophyte and one of the causal agents of fusariosis in human and animals. Their total antioxidant activity was measured using DPPH radical scavenging assay and their antimicrobial activity was determined through poison food assay at two concentrations (1000 and 1500 ppm) and spore germination assay in vitro. All methanolic extracts showed high antioxidant activity which among them methanolic extract of thyme demonstrated higher antioxidant potential with a low IC50 (16.50 mg ascorbic acid/g). Also, the highest phenolic content (70.55 mg GAE g-1) was observed in methanolic extract of thyme. The highest and lowest amount of thymol was determined in methanolic extract of thyme and aqueous extract of ajowan. Methanolic extracts of thyme leaves and ajowan seeds at concentration of 1500 ppm were potentially effective against F. solani over the control treatments by 90.33% and 85.73%, respectively. Followed by hydro-ethanolic and aqueous extracts exhibited a lesser percentage of inhibition. The MIC value for methanolic extract of thyme and ajowan was 3.75 mg/ml followed by hydro-ethanolic and aqueous extracts, respectively. The amount of calculated MFC was ranging from 7.5 to 30 mg/ml for thyme methanolic and fenugreek aqueous extracts, respectively.